Association of dietary live microbe intake with kidney stone disease in US adults: a real-world cross-sectional study - Zheng, Zhongyi; Cao, Xiaoming (Frontiers in Nutrition, 2024)
Backround: Kidney stone disease (KSD) is a common urological condition linked with hypertension, chronic kidney disease, and other health issues. Although the gut microbiome has a notable association with KSD formation, the relationship between dietary live microbes and KSD risk remains underexplored.Methods: This study utilized data from the NHANES surveys conducted between 2007 and 2016 to analyze the association between dietary live microbe intake and KSD. Dietary intake data were obtained through 24-hour dietary recall interviews conducted by trained professionals. Participants were categorized into three groups based on Sanders' classification system of dietary live microbe intake: low, medium, and high. The intake levels were determined by estimating the live microbe content in foods. Weighted logistic regression analysis was employed to account for the complex survey design and to assess the impact of different levels of live microbe intake on KSD risk.Results: A total of 20,380 participants were included in the study. Participants with low, medium, and high dietary microbe intake represented 33%, 39%,and 28% of the cohort, respectively.The adjusted odds ratios (ORs) for KSD were 0.78 (95% CI, 0.65-0.93) in the high dietary live microbe group compared to the low group (p < 0.05). Subgroup analyses revealed no significant interactions between dietary live microbe intake and gender, age, BMI, hypertension, or diabetes status.Higher dietary live microbe intake group may be associated with a reduced risk of KSD. Further prospective studies are necessary to validate these findings and to elucidate the specific mechanisms and optimal intake levels of dietary microbes.